Danau Laut Balbullol di Misool Raja Ampat - Gandi YS Purba; Eko Haryono; Sunarto Sunarto (Jurnal Sumberdaya Akuatik Indopasifik, 2017)
Marine lake is a unique ecosystem. It focuses at four locations in the world. One of them is in Raja Ampat. Each lake have a unique character according to the level of connection with the sea. Lake Balbullol is the deepest lake among the sea lakes in Misool, alienated, and has never been studied. This study want to know the character of Lake Balbullol. Description of the lake is done by a series of field surveys and loggers recording to determine the physical character, water quality, and presence of the biota. Lake width was 1.94 ha and the maximum depth was 38 m. Temperature and salinity showed a homogeneous vertical profile, thus forming a holomictic type. During 6 months time series, the temperature was always warmer than at the ocean, as well as salinity. Although the distance between the lake and the sea is very close (<45 m), the tide on the lake was delayed 4 hours rather than the sea. Tidal amplitude was only 25% of the ocean. From measurement of the tides showed Lake Balbullol was isolated lakes, however, there were no biota as an indicator of isolated lakes exist. There were at least 7 soft corals with attributes many and abundant exist in this lake.